2009
DOI: 10.1016/j.bpj.2009.06.030
|View full text |Cite
|
Sign up to set email alerts
|

The Control of the Controller: Molecular Mechanisms for Robust Perfect Adaptation and Temperature Compensation

Abstract: Organisms have the property to adapt to a changing environment and keep certain components within a cell regulated at the same level (homeostasis). "Perfect adaptation" describes an organism's response to an external stepwise perturbation by regulating some of its variables/components precisely to their original preperturbation values. Numerous examples of perfect adaptation/homeostasis have been found, as for example, in bacterial chemotaxis, photoreceptor responses, MAP kinase activities, or in metal-ion hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
145
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(148 citation statements)
references
References 45 publications
3
145
0
Order By: Relevance
“…5), the major difference between HT and PS models has not been reported or investigated, to our knowledge. Future work can also investigate whether PS models follow the entrainment properties [37,45,47,142,[156][157][158] or temperature compensation mechanisms [38,40,42,[159][160][161][162][163][164][165][166] identified with HT models. Furthermore, stochastic simulations of HT models commonly indicate that circadian clocks can maintain rhythms even with low numbers of molecules [167][168][169][170].…”
Section: Resultsmentioning
confidence: 99%
“…5), the major difference between HT and PS models has not been reported or investigated, to our knowledge. Future work can also investigate whether PS models follow the entrainment properties [37,45,47,142,[156][157][158] or temperature compensation mechanisms [38,40,42,[159][160][161][162][163][164][165][166] identified with HT models. Furthermore, stochastic simulations of HT models commonly indicate that circadian clocks can maintain rhythms even with low numbers of molecules [167][168][169][170].…”
Section: Resultsmentioning
confidence: 99%
“…With K 0.5 E set NaK Ͻ Ͻ n NaK (saturation) the degradation term is approximately constant at V max E set NaK , and thus ṅ NaK is zero when [Na c ] is at the setpoint V max E set NaK /k NaK . We have previously shown that zero-order kinetics is a sufficient condition for integral control (58). The outflow of Na ϩ is still given by the J NaK expression (Eq.…”
Section: Extending the Model To Test Regulatory Mechanismsmentioning
confidence: 99%
“…Mettetal et al [24] developed a concise model by using linear systems theory, and then revised this model arguing for the necessity of at least one branch of the system to implement integral control to achieve the experimentally observed adaptive responses in the system, Muzzey et al [26]. The role of integral feedback in perfectly adaptive systems is by now well-studied in the Systems Biology literature (see [26,27]), and it is highly likely that the osmoregulation system in yeast does indeed include a biochemical implementation of integral feedback, as seen in other systems (see [6,27,39]). It is still unclear, however, exactly how biological control systems such as osmoregulation might have evolved to use integral feedback control, and whether other alternative mechanisms might produce similar (or better) performance properties.…”
Section: Osmoregulation Process In Yeastmentioning
confidence: 99%
“…In particular, the experimental input, using a first harmonic approximation (see [5] pp. [26][27][28][29][30], can be written as…”
Section: A Lti System Identificationmentioning
confidence: 99%